Leadership styles of senior executives in business and government organizations: A comparative study - G. Chitayat; I. Venezia (South African Journal of Business Management, 1988)
This article has two main objectives. First, to analyse to what extent organizational differences affect the basic relationship between style of leadership and power and information. Second, to investigate whether the results (concerning leadership styles) previously obtained for middle and lower level management also hold true for senior executives, and if not, how these should be modified. More specifically, the effects of power and information on the leadership styles of senior executives are examined and compared with those found for lower level managers. For comparison with other studies, the styles chosen for analysis were: directive, negotiative, consultive, participative and delegative. It is shown that the effects of power and information on leadership styles are not the same across organizations. Power is positively correlated with directiveness in business organizations, but negatively correlated with this style of leadership in non-business organizations. The frequency of usage of certain leadership styles is shown to vary across organizations, and the implications of these variations are discussed. It is also demonstrated that the effects of power and information on leadership styles of senior executives do not differ considerably from the comparable effects found on lower level management.
Keywords: 650